Portugal : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
The staff report for the 2005 Article IV Consultation on Portugal highlights economic developments and outlook. Private consumption has proven resilient, reflecting low interest rates and lengthening tenors on bank lending, while investment and export growth remained weak. Executive Directors concurred that in an unfavorable context marked by large fiscal and external imbalances, slow growth, and a weak competitive position, the challenge confronting the Portuguese government is to create the conditions to restart Portugal's per capita income convergence toward the euro area average as soon as possible.